Effect of Environmental Parameters on the Performance of Optical Wireless Communications. (2nd May 2019) - Ali, Hosam Abd Elrazek Mohamed; Said, El-Sayed Soliman A.; Yousef, Mohamed Ebrahim
Abstract : Free space optical communication systems are the future of the communication systems which can meet the needs of the end users who are demanding high bandwidths to support high-speed communication. These merits are due to its numerous advantages as well as their better performance. This paper studies the effect of environmental parameters like rain, fog, haze, snow, and dust on the performance of optical wireless communications using Opti-system program. This work considers the effect of visibility as well as operating wavelengths on atmospheric attenuation in different weather conditions for free space optical link. For different weather conditions the max distance between transmitter and receiver can also be estimated. The system analysis depicted the better performance of the Multi-Input/Multi-Output (MIMO) configurations compared to Single Input/Single Output (SISO) at different weather conditions.